Beyond the androgen receptor II: New approaches to understanding and treating metastatic prostate cancer; Report from the 2017 Coffey‐Holden Prostate Cancer Academy Meeting. Issue 15 (18th September 2017) - Miyahira, Andrea K.; Cheng, Heather H.; Abida, Wassim; Ellis, Leigh; Harshman, Lauren C.; Spratt, Daniel E.; Simons, Jonathan W.; Pienta, Kenneth J.; Soule, Howard R.
Abstract : Introduction: The 2017 Coffey‐Holden Prostate Cancer Academy (CHPCA) Meeting, "Beyond the Androgen Receptor II: New Approaches to Understanding and Treating Metastatic Prostate Cancer, " was held in Carlsbad, California from June 14‐17, 2017. Methods: The CHPCA is an annual scientific conference hosted by the Prostate Cancer Foundation (PCF) that is uniquely designed to produce extensive and constructive discussions on the most urgent and impactful topics concerning research into the biology and treatment of metastatic prostate cancer. The 2017 CHPCA Meeting was the 5th meeting in this annual series and was attended by 71 investigators focused on prostate cancer and a variety of other fields including breast and ovarian cancer. Results: The discussions at the meeting were concentrated on topics areas including: mechanisms and therapeutic approaches for molecular subclasses of castrate resistant prostate cancer (CRPC), the epigenetic landscape of prostate cancer, the role of DNA repair gene mutations, advancing the use of germline genetics in clinical practice, radionuclides for imaging and therapy, advances in molecular imaging, and therapeutic strategies for successful use of immunotherapy in advanced prostate cancer. Discussion: This article reviews the presentations and discussions from the 2017 CHPCA Meeting in order to disseminate this knowledge and accelerate new biological understandings and advances in the treatment of patients with metastatic prostate cancer.